Residential care, stigma and relational alienation: exploring the lived experience of children’s homes with young people and carers - an ethnographic study - Woods, Helen Y. (2020)
This thesis questions both social meaning and lived experience of residential care for children, by drawing on data gathered during an ethnographic study of two local authority children’s homes. Theories of ‘social death’ are utilised to understand the social relationships of children and young people. Children’s homes continue to be a site of research and intervention in the UK and elsewhere. The established view of residential care in the UK is that it is the ‘last resort’ option for children in the care system, due to the preference for family-based accommodation. Recently, while there has been greater acknowledgement that residential care can be a positive choice for children, the sector continues to be a site of controversy. This is due to factors such as abuse scandals, poor outcome measures, placement breakdowns and cost effectiveness. A number of studies reveal that young people cite placement instability as a key factor which negatively affects their experience. Those in residential care are likely to experience the greatest upheaval in the care system. Drawing on the work of Ennew (2002), this thesis proposes that such factors combine to affect the personhood of children in residential settings due to the children’s home contrasting to normative ideals of what children ought to experience in the context of childhood. Data reveals that the absence of enduring relationships within children’s home is deeply problematic in terms of the social, psychological and symbolic status of children and young people. Findings also promote a critical stance to the individualising of children in care and the ability of the rights framework to compensate for wider losses. Building on Orlando Patterson’s (1982) work on social death the concept of ‘relational alienation’ is developed as an original theoretical contribution to knowledge, to comprehend the loss of relational life and personhood which children and young people experience in residential care. The thesis concludes with recommendations aimed at reducing the risk of social death for children in care and residential care.